(untitled) (Boletim de Geografia, 2012)
The environmental impacts of sand mining in hillsides of the North of Minas Gerais State have led to social unrests, discussed at Minas Gerais State North Regional Collegiate Unity of the State Council of Environmental Policy – COPAM. Aiming at better supporting the discussions and bringing about proposals to the conflict resolution, an environmental vulnerability zoning related to such undertakings was elaborated. This zoning considered variables derived from topography, land use, ecosystems and from the synergy of those impacts on the hydrographic network. Means to achieve the sustainable development of the mining works aiming at the civil construction industry are suggested after analyzing the obtained product.